Synthesis of Phenanthrenol Derivatives Through Polar Diels-Alder Reactions Employing Nitronaphthalenes and (E)-1-(Trimethylsilyloxy)-1,3- butadiene. Theoretical Calculations - Kneeteman, Maria Nelida (2014)
The cycloaddition reactions between nitronaphthalenes and 1-trimethylsilyloxy-1,3-butadiene produce phenantrenol derivatives as principal products. The primary adducts suffer the irreversible lost of nitrous acid and consequently, the aromatization. In these reactions it is frequent to observe the presence of naphtylpyrrole derivatives as a result of a hetero Diels-Alder process, which is competitive with the normal way. The global electrophilic character of the dienophile is responsible of these results. Other dienes with electron donor substitution in C-1 show a different behavior in which the hetero Diels-Alder products prevails. In the series explored only the substrate 1-ciano-4-nitronaphthalene produces the naphtylpyrrole derivative as principal product, probably as a consequence of its charge distribution. A combination between stereoelectronic effects in the electrophile and the type of substitution joint to the nucleophilicity of the diene is responsible of the results and regioselectivity observed in these polar cycloaddition reactions. In all the cases studied the regioselectivity expected by theoretical calculations corresponds with the ones obtained experimentally.